2010
DOI: 10.1246/cl.2011.31
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Amylose–Poly(tetrahydrofuran) Inclusion Complexes in Ionic Liquid Media

Abstract: In this study, we found that amylose–poly(tetrahydrofuran) (PTHF) inclusion complexes were formed when a mixture of amylose with PTHF was stirred in 1-butyl-3-methylimidazolium chloride of an ionic liquid at high temperature under reduced pressure, followed by cooling and precipitation by addition of methanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
2

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…[1][2][3][4][5][6][7] However, only limited research has been reported regarding the formation of inclusion complexes between amylose and polymeric compounds. [8][9][10][11][12][13][14] Amylose in solid-state constructs stabilized crystalline structures associated with the formation of double helixes. 15 In addition, single-stranded amylose in an aqueous solution gradually forms a double helix, resulting in a water-insoluble product.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] However, only limited research has been reported regarding the formation of inclusion complexes between amylose and polymeric compounds. [8][9][10][11][12][13][14] Amylose in solid-state constructs stabilized crystalline structures associated with the formation of double helixes. 15 In addition, single-stranded amylose in an aqueous solution gradually forms a double helix, resulting in a water-insoluble product.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, hydrophobicity is required as the property of guest molecules to be included by amylose. However, only limited studies had been reported regarding the formation of inclusion complexes composed of amylose and polymeric guest molecules [23][24][25][26][27][28][29]. Because the driving force incorporating guest molecules into the cavity of amylose is the weak hydrophobic interaction, amylose does not have sufficient ability to include the long chains of polymeric guests into its cavity.…”
Section: Introductionmentioning
confidence: 99%
“…This is composed of glucose residues linked through α-(1 → 4)-glucosidic bonds. Although inclusion nanocomplexes of amylose with polymeric guest compounds are also interesting as functional eco-friendly polymeric materials, only limited studies have been reported regarding the direct complexation of amylose and polymeric molecules (Frampton et al 2008;Ikeda et al 2006;Kaneko et al 2011a;Kida et al 2007Kida et al , 2008Shogren 1993;Shogren et al 1991). The driving force for complexation of guest molecules in the cavity is mainly hydrophobic interaction as the inside of the amylose helix has a hydrophobic nature due to the presence of hydrophilic hydroxy groups in the glucose residues on outer part of the helix.…”
Section: Discussionmentioning
confidence: 99%